Analytical Hierarchy Process for Optimizing Shorebase Cost: A Case Study in East Java Offshore National Oil & Gas Company - Dhanang Resnamurti; Yuniningsih Yuniningsih; Dwi Suhartini; Wiwik Handayani (Eduvest - Journal of Universal Studies, 2025)
This research addresses the need to optimize shorebase logistics costs for the East Java Offshore National Oil & Gas Company amid declining production and rising operational expenses. The study aims to determine the most efficient shorebase operation method by evaluating three alternatives: maintaining the current rental warehouse in Lamongan, relocating to a company-owned warehouse in Cepu, or moving to another rental warehouse in Gresik. Using a Multi-Criteria Decision-Making (MCDM) approach with the Analytical Hierarchy Process (AHP), data were collected through Focus Group Discussions with supply chain experts and surveys from competent respondents. Key criteria included operation cost, mobilization cost, and handling efficiency. Results indicate that maintaining the existing Lamongan shorebase is the optimal choice, followed by relocating to the owned warehouse. The study demonstrates the applicability of AHP in integrating quantitative and qualitative factors for strategic logistics decision-making, with implications for cost efficiency and operational stability in upstream oil and gas operations.